Desain UI/UX Aplikasi Website Pemesanan Foto Studio Menggunakan Metode Design Thinking - Nurani, Sutra; Ruly Dwi Arista; Hermansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The advancement of digital technology has significantly transformed consumer behavior in accessing and booking services, including in the photography sector. Maka Studio, as a provider of professional photography services, requires a digital platform in the form of a website application that offers an intuitive user interface (UI) and an optimal user experience (UX). This study aims to design the UI/UX of a web-based photography service booking application using the Design Thinking method, which emphasizes a user-centered approach. The design process follows five key stages: empathize, define, ideate, prototype, and test. Data collection was carried out through interviews and observations to identify users’ pain points, which were then translated into visual solutions in the form of wireframes and interactive prototypes using Figma. The main features of the application include service exploration, schedule selection, booking, and payment simulation. The prototype was tested by ten respondents representing the target users to evaluate usability, user flow clarity, and visual satisfaction. The results indicated that the interface design successfully met user expectations, achieving an average System Usability Scale (SUS) score of 93.75, categorized as excellent. These findings affirm that a user-centered design approach is effective in producing functional, efficient, and user-preferred digital solutions.